Effects of Temperature on Methanogenesis in a Thermophilic (58°C) Anaerobic Digestor - Zinder, S. H. (1984)
The short-term effects of temperature on methanogenesis from acetate or CO(2) in a thermophilic (58°C) anaerobic digestor were studied by incubating digestor sludge at different temperatures with (14)C-labeled methane precursors ((14)CH(3)COO(−) or (14)CO(2)). During a period when Methanosarcina sp. was numerous in the sludge, methanogenesis from acetate was optimal at 55 to 60°C and was completely inhibited at 65°C. A Methanosarcina culture isolated from the digestor grew optimally on acetate at 55 to 58°C and did not grow or produce methane at 65°C. An accidental shift of digestor temperature from 58 to 64°C during this period caused a sharp decrease in gas production and a large increase in acetate concentration within 24 h, indicating that the aceticlastic methanogens in the digestor were the population most susceptible to this temperature increase. During a later period when Methanothrix sp. was numerous in the digestor, methanogenesis from (14)CH(3)COO(−) was optimal at 65°C and completely inhibited at 75°C. A partially purified Methanothrix enrichment culture derived from the digestor had a maximum growth temperature near 70°C. Methanogenesis from (14)CO(2) in the sludge was optimal at 65°C and still proceeded at 75°C. A CO(2)-reducing Methanobacterium sp. isolated from the digestor was capable of methanogenesis at 75°C. During the period when Methanothix sp. was apparently dominant, sludge incubated for 24 h at 65°C produced more methane than sludge incubated at 60°C, and no acetate accumulated at 65°C. Methanogenesis was severely inhibited in sludge incubated at 70°C, but since neither acetate nor H(2) accumulated, production of these methanogenic substrates by fermentative bacteria was probably the most temperature-sensitive process. Thus, there was a correlation between digestor performance at different temperatures and responses to temperature by cultures of methanogens believed to play important roles in the digestor.